Comparison of the essential oil components in fresh peels of lime (citrus aurantifolia) extracted with supercritical fluid extraction and other three traditional extraction methods - Muhd Zin, Nur Huda; Abd Hamid, Shafida; Wan Abdul Khodir, Wan Kartini; Aminudin, Nurul Iman; Danial, Wan Hazman; Bakhtiar, M. Taher; Darnis, Deny Susanti (2018)
Citrus is one of the famous crops that widely cultivated and is the most commonly utilized fruits in the world due to its pleasant taste and nutritional value. Citrus essential oil is also highly in demand by consumer but the production cost is quite expensive as it produced in very low quantity. Moreover, the chemical compositions in citrus essential oil influence its biological activity such as antioxidant, germicidal, antifungi and antimicrobial. Unfortunately, there is lack of information comparing the chemical components in Citrus aurantifolia essential oils extracted using different methods. In this study the peels of C. aurantifolia fruits were extracted using hydro-distillation, steam-distillation, solvent extraction and supercritical fluid extraction (SFE) techniques and the chemical composition was compared using Gas Chromatography-Mass Spectrometry (GC-MS) and Gas Chromatography-Flame Ionization Detector (GC-FID). The main components in the essential oils from hydro-distillation and steam-distillation were (+)-limonene, (-)-β-pinene and α-citral with leden oxide (II) and 5α-cholestan-3β-ol, 2-methylene were also present in the essential oil from steam-distillation process. While, ethyl iso-allocholate, citraptene, D:C-friedours-7-ene-3-one, herniarin, and isopimpinellin were the major components present in the essential oil from solvent extraction method. In SFE extraction, the main chemical compounds in peel of C. aurantifolia were 7,9-di-tert-butyl-1-oxaspiro(4,5)deca-6,9-diene-2,8-dione, citraptene, isopimpinellin, and herniarin. The results show that monoterpene was the major component in hydro-distillation and steam-distillation while, coumarin was the major component in solvent extraction and SFE methods. The results also indicate that different extraction methods used produce different yield and chemical constituents. The percentage yield and major class of component of fresh peels C. aurantifolia using different methods were significantly different (p<0.05). However, there was no significance difference (p>0.05) in extraction methods used in total chemical composition in C. aurantifolia essential oils.